Gender-specific association between carbohydrate consumption and blood pressure in Chinese adults - Qiang Li (BMJ Nutrition, Prevention & Health)
Background The association between dietary carbohydrate consumption and blood pressure (BP) is controversial. The present study aimed to evaluate the possible gender-specific association of carbohydrate across the whole BP distribution.Method Cross-sectional survey including 2241 rural adults was conducted in northwestern China in 2010. BP was measured by trained medical personnel. Dietary information was collected by semiquantitative Food-Frequency Questionnaire. Multivariate quantile regression model was used to estimate the association between total carbohydrates consumption and systolic BP (SBP) and diastolic BP (DBP) at different quantiles. Gender-specific β coefficient and its 95% CI was calculated.Results The average carbohydrate intake was 267.4 (SD 112.0) g/day in males and 204.9 (SD 90.7) g/day in females, with only 10.6% of males and 6.5% females consumed at least 65% of total energy from carbohydrates. And more than 80% carbohydrates were derived from refined grains. In females, increased total carbohydrates intake was associated with adverse SBP and DBP. An additional 50 g carbohydrates per day was positively associated with SBP at low and high quantiles (10th–20th and 60th–80th) and with DBP almost across whole distribution (30th–90th), after adjusting for age, fortune index, family history of hypertension, body mass index, physical activity level, alcohol intake and smoke, energy, two nutrient principal components, protein and sodium intake. Both relatively low and high carbohydrate intake were associated with increased SBP, with minimum level observed at 130–150 g carbohydrate intake per day from restricted cubic splines. However, no significant associations were observed in males.Conclusions Higher total carbohydrates consumption might have an adverse impact on both SBP and DBP in Chinese females but not males. Additionally, the positive association varies across distribution of BP quantiles. Further research is warranted to validate these findings and clarify the causality.